AN EMPIRICAL STUDY ON WORK LIFE BALANCE AMONG WOMEN TEACHING STAFF IN PRIVATE COLLEGES,BENGALURU - Mr. C B Gopinath; Ms. Mamatha G; Mr. Sridhar M (The journal of contemporary issues in business and government, 2022)
The purpose of this study is to assess the work-life balance of female teaching staff in private degree colleges in north Bangalore, Karnataka. Furthermore, this study assesses the level of work-life balance among female teaching staff members and examines the impact of various socio-demographic characteristics on their work-life balance. A total of 112 samples were chosen, and data was collected using the questionnaire method, with the data analysed using a social science statistical software (SPSS). According to the study’s findings, more than half of women teaching staff members have a good degree of work-life balance, while more than a quarter of women teaching staff members have a low level of work-life balance. According to the findings, there is a statistically significant link between women teaching staff members’ monthly pay and work-life balance.